2020
DOI: 10.18008/1816-5095-2020-4-824-829
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of PCR in Diagnosis of Fungal Keratitis

Abstract: Fungi implicated in mycotic keratitis include different species. Conventional methods for the diagnosis of fungal keratitis include staining of corneal scarpings, culture medium (Sabouraud agar) for isolating fungi.Purpose. To evaluate the effectiveness of polymerase chain reaction (PCR) for the detection of fungal etiology in comparison with the conventional diagnostic methods in cases with suspected fungal corneal ulcer.Patients and methods. Seven patients with severe corneal ulcers with more than 3 weeks du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Genus and sometimes species of the causative agent are identified by specific appearance of the colony (color, shape, consistency, spore availability, hypha, pseudohypha). This method is considered the golden standard of the diagnosis, is easy enough, and cost-effective, but still having some limitations: difficulty of species diagnosis, long response time (about a week) [ 80 , 81 ], dependence on the researcher experience, non-typical morphology of some colonies, insufficient knowledge of the suitable conditions of cultivation, inaccessibility of stromal layers for corneal scraping in case of deep fungal penetration [ 82 ], false-negative results of inoculation in case of insufficient scraping volume or progression of corneal destruction, the effect of the previous empirical therapy on the inoculation results [ 83 ]. For example, one of the studies [ 84 ] reported negative results of inoculation and unestablished laboratory diagnoses in 37% of patients with fungal keratitis explaining the reason by antibiotic therapy administered before the admission to the hospital.…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Genus and sometimes species of the causative agent are identified by specific appearance of the colony (color, shape, consistency, spore availability, hypha, pseudohypha). This method is considered the golden standard of the diagnosis, is easy enough, and cost-effective, but still having some limitations: difficulty of species diagnosis, long response time (about a week) [ 80 , 81 ], dependence on the researcher experience, non-typical morphology of some colonies, insufficient knowledge of the suitable conditions of cultivation, inaccessibility of stromal layers for corneal scraping in case of deep fungal penetration [ 82 ], false-negative results of inoculation in case of insufficient scraping volume or progression of corneal destruction, the effect of the previous empirical therapy on the inoculation results [ 83 ]. For example, one of the studies [ 84 ] reported negative results of inoculation and unestablished laboratory diagnoses in 37% of patients with fungal keratitis explaining the reason by antibiotic therapy administered before the admission to the hospital.…”
Section: Diagnosismentioning
confidence: 99%
“…The advantages of PCR are indisputable: the results may be obtained within 4 h instead of 3–7 days in cultural investigations; the method is highly sensible enabling to detect a pathogen in a small scrape from the corneal ulcer or the material from patients receiving previously antifungal therapy [ 81 ]. Like other molecular genetic methods, PCR is designed for species identification.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation